Cancer prevention, risk reduction, and control: opportunities for the next decade of health care delivery research. Issue 11 (30th November 2021) - O'Malley, Denalee M; Alfano, Catherine M; Doose, Michelle; Kinney, Anita Y; Lee, Simon J Craddock; Nekhlyudov, Larissa; Duberstein, Paul; Hudson, Shawna V
Abstract: In this commentary, we discuss opportunities to optimize cancer care delivery in the next decade building from evidence and advancements in the conceptualization and implementation of multi-level translational behavioral interventions. We summarize critical issues and discoveries describing new directions for translational behavioral research in the coming decade based on the promise of the accelerated application of this evidence within learning health systems. To illustrate these advances, we discuss cancer prevention, risk reduction (particularly precision prevention and early detection), and cancer treatment and survivorship (particularly risk- and need-stratified comprehensive care) and propose opportunities to equitably improve outcomes while addressing clinician shortages and cross-system coordination. We also discuss the impacts of COVID-19 and potential advances of scientific knowledge in the context of existing evidence, the need for adaptation, and potential areas of innovation to meet the needs of converging crises (e.g., fragmented care, workforce shortages, ongoing pandemic) in cancer health care delivery. Finally, we discuss new areas for exploration by applying key lessons gleaned from implementation efforts guided by advances in behavioral health.